¿Quién es el juez de los derechos fundamentales frente a la ley en el ámbito interno de aplicación del derecho comunitario?: (reflexiones sobre el control iusfundamental del derecho interno a la luz de la recepción nacional de los derechos fundamentales d - Ugartemendia Eceizabarrena, Juan Ignacio (Teoría y Realidad Constitucional, 2007)
The aim of this article is firstly to describe the phenomenum of «national or state incorporation« of European Union Fundamental Rights.That is a process that was launched by the European Court of Justice with its judgment Wachauf in 1989, when it established that Member states were obliged to respect European Community Fundamental Rights in the implementation of Community law rules. It implies that those afore mentioned rights become parameters of conformity with Community Law and are to be used by national courts and judges when they are asked to control national authorities’ acts (including national legislure’s) taking into account those parameters. From this point of view, this work tries likewise to analyse how that incorporation affects the activity of judicial review of national acts in the light of fundamental rights as recognized by the National constitution. And specially when judicial review deals with Acts and other legal rules with same rank.